FILSAFAT AKHLAK DALAM PEMIKIRAN ETIKA KONTEMPORER - Eka Damayanti; Aliman; Hamsah F (Faculty of Tarbiyah and Teacher Training, 2022)
This article aims to outline the response of akhlaq philosophy to contemporary ethical thought. Library research is carried out by collecting data sources from books, and journals and other scientific articles. The data were analyzed using content analysis (content analisys). The results showed that filasafat akhlaq and ethical philosophy have a relationship, namely both studying the concept of good or bad values, as well as right and wrong. The fundamental difference between akhlaq philosophy and ethics is from the source of reference. Akhlaq refers to revelation and ethics refers to rationality.